REVERSIBLE PUMP-TURBINES – A STUDY OF PUMPING MODE OFF-DESIGN CONDITIONS - Ješe, Uroš; Skotak, Aleš (Journal of Energy Technology, 2024)
The role of pumped storage power plants (PSP) in electrical grid systems has been changing in recent years. Demands for switching from pumping to generating mode are becoming increasingly frequent. Moreover, the operating ranges of the reversible pump-turbines used in PSP systems are becoming wider in order to use the PSP as a regulator and a stabilizer of the electrical grid. The primary challenges in the development of pump-turbines are the hydraulic instabilities that occur in pumping and generating modes. The present paper focuses on partial load pumping mode instabilities, such as cavitation and rotating stall. Modern tools, such as CFD, are used for the analysis of the phenomena along with conventional experimental approaches. Rotating stall has been investigated in hydraulic laboratory experimentally and reproduced numerically using commercial CFD code. Three rotating stall cells with a rotational frequency of 2.5% of nominal pump-turbine frequency have been identified. Cavitat- ing vortices related to rotating stall were found in the guide vanes region. Both phenomena indicate highly unstable and potentially dangerous operating conditions that need to be investigated in detail. Understanding the causes for the instabilities will lead to an improved pump-turbine design that will enable safer, more flexible and more reliable operating with fewer unwanted instabilities.